Republic of Mozambique : 2009 Article IV Consultation, Fourth Review Under the Policy Support Instrument, and Request for a Twelve-Month Arrangement Under the Exogenous Shocks Facility; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that against a backdrop of a highly uncertain global economic environment, Mozambique's macroeconomic prospects remain positive, but have weakened. The scope for supportive macroeconomic policies to offset the impact of the global economic slowdown is curtailed by the large projected decline in external reserves. Executive Directors have welcomed Mozambique's continued strong macroeconomic performance in 2008. Directors have also commended the authorities' flexible policy response to higher fuel and food import prices, which has helped to mitigate the impact of these shocks.